2013
DOI: 10.1519/jpt.0b013e318282d2f1
|View full text |Cite
|
Sign up to set email alerts
|

True or Apparent Leg Length Discrepancy

Abstract: Apparent LLD can be a better predictor of patient-perceived inequality and physical performance than true LLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Through PubMed, we found only a few reports focusing on this phenomenon. [ 4 8 11 12 13 ] Among them, only one study revealed the relationship between PO and its influences on the acetabular component orientation during surgery,[ 4 ] which was also from our institution. There were many studies focused on the variation in the pelvic tilt angle after THA surgery and its influences on the prosthetic orientation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through PubMed, we found only a few reports focusing on this phenomenon. [ 4 8 11 12 13 ] Among them, only one study revealed the relationship between PO and its influences on the acetabular component orientation during surgery,[ 4 ] which was also from our institution. There were many studies focused on the variation in the pelvic tilt angle after THA surgery and its influences on the prosthetic orientation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 ] Suprapelvic obliquity is usually originated from spinal disease, and only intra-PO can be corrected by THA surgery; therefore, our research focused primarily on intra-PO, which can lead to apparent LLD, as noted by some Japanese researchers. [ 6 7 8 ] Through surgery, intra-PO had been corrected. Aside from suprapelvic obliquity, intra-PO is the most important cause of LLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two percent, 11%, and 7% of patients complain of a sense of surgical leg prolongation—a perceived leg length discrepancy (PLLD)—beyond the radiographic leg length discrepancy who underwent unilateral THA at 3 weeks, 3 months, and 1 year postoperatively, respectively 11 ) . The PLLD after unilateral THA can often be caused by a pelvic tilt as a result of a functional leg length discrepancy (LLD) 12 ) . Compared with patients without PLLD, THA patients with PLLD after unilateral THA have a smaller hip adduction range of motion during gait 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Based on etiology, LLD can be conceptualized as falling into one of two main categories: 1) structural or ‘true’ LLD and 2) functional or ‘apparent’ LLD [24, 25]. True LLD is attributable to actual shortening of bony structures, usually as a result of defective pelvic or femoral anatomy.…”
Section: Introductionmentioning
confidence: 99%